2012
DOI: 10.1111/j.1574-6941.2012.01316.x
|View full text |Cite
|
Sign up to set email alerts
|

Spatio-temporal niche partitioning of closely related picocyanobacteria clades and phycocyanin pigment types in Lake Constance (Germany)

Abstract: We found that the clade-specific abundance dynamics of Synechococcus type picocyanobacteria in the pelagic and littoral zone macro-habitats of Lake Constance (Germany) challenge the hypothesis of a regular annual succession of picocyanobacteria genotypes in temperate zone lakes. Methods used in this study were quantitative Taq nuclease assays (TNA), denaturing gradient gel electrophoresis (DGGE), a 19-month time series analysis (with two isothermal and two stratified periods) and genotyping of a new littoral p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 55 publications
1
13
0
Order By: Relevance
“…Whereas temporal and spatial heterogeneity in environmental conditions can increase biodiversity [76], [77], the KtW-model predicts coexistence also at steady state. Hence it adds to the understanding of the paradox of plankton [18], including prokaryotes.…”
Section: Discussionmentioning
confidence: 96%
“…Whereas temporal and spatial heterogeneity in environmental conditions can increase biodiversity [76], [77], the KtW-model predicts coexistence also at steady state. Hence it adds to the understanding of the paradox of plankton [18], including prokaryotes.…”
Section: Discussionmentioning
confidence: 96%
“…). This reflects similar studies that demonstrate that algal or particle‐associated communities differ from water column communities (Weiss et al ., ; Steven et al ., ; Becker et al ., ). This indicates that plastid 23S was able to recapitulate previously described niche partitioning of algal communities and can be employed to differentiate algal communities that differ between habitats in the same environment or along environmental gradients.…”
Section: Discussionmentioning
confidence: 97%
“…Initially, such studies were limited to analyses of cultured strains [15,16,18,31], but the advent of denaturing gradient gel electrophoresis (DGGE) made it possible to characterize DNA in situ, without the need to isolate and cultivate the organisms [3,5,9,33]. Despite this technical advance, there remains a dearth of available information about seasonal changes, geographic distribution, and community structure of picocyanobacteria in various types of water bodies [4]. Some studies suggest clear seasonal changes in picocyanobacteria, resembling those observed in larger phytoplankton [17].…”
mentioning
confidence: 99%